Travel discontinuities, enforced holidaying-at-home and alternative leisure travel futures after COVID-19. Issue 2 (3rd April 2023) - Jacobsen, Jens Kr. Steen; Farstad, Eivind; Higham, James; Hopkins, Debbie; Landa-Mata, Iratxe
Abstract: The paralysis of global tourism caused by COVID-19 made it possible to conduct a unique and nearly real-time online survey to investigate adaptations and reactions to sudden severe leisure travel restrictions among residents in the Oslo metropolitan area of Norway during the 2020 Easter/spring holiday period. Stress relief, socialising, social bonds and discoveries of local recreation options were important home holiday experiences. Vacation challenges under lockdown included few opportunities for novelty and the chance of liminoid situations – reversal or bracketing of everyday routine existence. The enforced Easter staycation advanced reflections on impending leisure travel, indicating limited opportunities to boost future low-carbon near-home Easter holiday experiences. Path dependencies towards second homes and spatially stretched social obligations, as well as emphasis on freedom of movement, ostensibly constrain vacation travel habit discontinuities at this time of the year.